(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The paper considers the variation o f annual ring parameters and physical properties of wood of the pine species prevailing in Latvia’s forests, depending on the forest type (bog-land, vacciniosa) and the growth region in Latvia (Vidzeme, Latgale). Wood samples were taken from the stem butt-end, the middle and 3 A o f the height, in its sapwood or core part. An average annual ring width, latewood and earlywood width in the year ring, the percentage of latewood in the annual ring, wood density in oven-dry state (0), tangential swelling (tg) and radial swelling (rad) o f wood, as well as volume swelling (v) and swelling anisotropy coefficient (k) o f wood were determined for the samples. A comparison of these data shows that, in the majority of cases, the indices for the wood of pines grown in vacciniose have higher values, which suggests the advantage of pine wood over the bog-land pine wood. In its turn, no unambiguous distinctions between the parameter values for pine wood o f Latgale and Vidzeme origin were found, although the pine wood of Vidzeme origin had a somewhat higher indices. It may be concluded that the greatest impact on the leading pine wood properties is caused by the forest types regarded herewith, and not the belonging o f the pine wood site to its different growth regions in Latvia.